Analysis of Clinical Pharmacy Interventions in Surgical Antibiotic Prophylaxis for Clean Orthopedic Surgery at Hong Ngoc – Phuc Truong Minh General Hospital - Dao Thi Lanh; Le Quang Huy; Nguyen Thi Thuy; Tran Thu Phuong; Phung Chi Kien; Nguyen Hoang Anh; Nguyen Thanh Hai (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Objectives: To analyze the actual situation and evaluate the clinical pharmacy interventions in prophylaxis antibiotics (PAB) usage for clean orthopedic surgery at Hong Ngoc – Phuc Truong Minh General Hospital. Subject and methods: Prospective descriptive study based on data collected from medical records and clinical pharmacy interventions related to prescribing and medication administration practices of healthcare staff in patients using prophylaxis antibiotics at the Department of Orthopedics – Neurosurgery, Hong Ngoc – Phuc Truong Minh General Hospital from 07/04/2025 to 31/08/2025. Characteristics of PAB use and the reasonable rate of PAB usage were assessed based on the Hospital’s Guidelines issued on 02/04/2025. Results: The study included 78 patients with a mean age of 43.08 years and a mean BMI of 23.84 kg/m²; 52.56% were male and 78.21% had ASA I status (followed American Society of Anesthesiologists). Cefazolin administered intravenously was used for surgical antibiotic prophylaxis in 100% of clean surgeries. Postoperatively, 98.72% of surgical wounds remained stable, and the incidence of surgical site infection during hospitalization was 2.56%. The overall compliance with all PAB protocol criteria was 85.90%, with 100% adherence regarding indication, dosage, route of administration, and intraoperative redosing. All medication-related problems associated with surgical antibiotic prophylaxis were identified and addressed by clinical pharmacists through direct communication with physicians and recommendations for antibiotic adjustment or discontinuation. Conclusion: The study showed relatively appropriate use of surgical antibiotic prophylaxis guidelines. All identified medication-related problems were reviewed and discussed by clinical pharmacists with physicians, mainly through direct communication and recommendations for antibiotic adjustment or discontinuation.